REFLECTING ON THE CHALLENGES IN CONSTRUCTING HIGH SCHOOL TRAINING ITINERARIES IN THE AMAZON CONTEXT, IN LIGHT OF LAW NO. 14.945/2024 - da Silva, Maurício Oliveira; Ayres, Carla Carol Pinto; Soares, Alfredo Taveira; de Fátima Vasconcelos Pinto, Klyssia (Seven Editora, 2025)
This study investigates the challenges in developing and implementing high school training itineraries in the Amazon region, based on the guidelines established by Law 14.945/2024 and regional specificities. The theme emerges from the need to adapt the curriculum to legal requirements while respecting the socio-environmental and cultural specificities of the Amazon. The overall objective was to investigate the challenges in developing and implementing high school training itineraries in the Amazon region, based on the guidelines established by Law 14.945/2024 and regional specificities. A qualitative and bibliographic methodology was adopted, guided by the deductive method. A systematic literature review (2019–2025) was conducted in databases such as SciELO, Google Academic, and CAPES Periódicos, selecting publications that addressed training itineraries, high school reform, and the Amazon region. The extracted data were organized into analytical categories (planning, challenges, and impacts) and analyzed using Bardin’s content analysis. The results revealed that the autonomy granted by Law 14.945/2024 drives shared governance initiatives, ongoing teacher training, and the use of informal spaces. However, infrastructure limitations (laboratories, connectivity), training, and community engagement hinder the implementation of the itineraries. Pedagogical barriers were identified, such as resistance to interdisciplinarity, and sociocultural barriers, such as the integration of traditional knowledge. It is concluded that overcoming these challenges requires integrated public policies, technical and financial resources, and the development of a culture of innovation and democratic management. The connection between schools, universities, and communities emerges as a prerequisite for legal guidelines to be converted into contextualized and transformative educational practices. DOI: https://doi.org/10.56238/sevened2025.030-022